we have point (-6, - 1)
Now we will put these points in each equation,
y = 4x +23
put x = -6 and y = -1
-1 = 4 (-6) +23
-1 = -24 + 23
-1 = -1
LHS = RHS, so this equation has (-6 , -1) as solution.
y = 6x
put x = -6 and y = -1
-1 = 6 (-6)
-1 not= -36
LHS is not equal RHS, so (-6 , -1) is not a solution for that equation,
y = 3x - 5
put x = -6 and y = -1
-1 = 3 (-6) - 5
-1 = -18 - 5
-1 not= -23
LHS is not equal RHS, so (-6 , -1) is not a solution for that equation,
y= 1/6 x
put x = -6 and y = -1
-1 = -6/6
-1 = -1
LHS = RHS, so (-6 , -1) is a solution for that equation,
Hello from MrBillDoesMath!
Answer:
fourthroot(35)
Discussion:
The question is a bit unclear as to the desired answer.... but here goes!
(35)^1/4 is the fourth root of 35, that is, symbolically, fourthroot(35).
Note the fourth root of a number is the same as the square root of the square root of the number.
Regards,
MrB
P.S. I'll be on vacation from Friday, Dec 22 to Jan 2, 2019. Have a Great New Year!
Add the two together and divide the answer by 137.16 add it together
-7 is the missing exponent